The Young Schema Questionnaire Short Form 3 (YSQ-S3): does the new four-domains model show the best fit? - Aloi, Matteo; Rania, Marianna; Sacco, Raffaella; Basile, Barbara; Segura-Garcia, Cristina (Anales de Psicología / Annals of Psychology, 2020)
The existence of early maladaptive schemas (EMS) is the core concept of Schema Therapy (ST). Several studies have demonstrated that EMSs are involved in many psychiatric disorders. The Young Schema Questionnaire is a self-report measure developed to assess the 18 EMSs and has long form (YSQ-L) and short form (YSQ-S) versions. It is currently in its third version (YSQ-S3). To the best of our knowledge, this is the first study that aims to validate the YSQ-S3 according to the new proposed organization of EMSs into four domains. A non clinical sample of 1372 Italian population was involved in this research. Confirmatory Factor Analysis (CFA) was conducted to examine the latent structure of the YSQ-S3, including both first- and second-order structures. Cronbach’s alpha and intra-class correlation coefficients were calculated to evaluate internal consistency and test-retest reliability. Correlations between the YSQ-S3 and anxiety and mood symptoms were calculated to measure construct validity. Cronbach’s alpha of almost all EMSs were higher than 0.7, which indicated good internal reliability, and test-retest reliability was excellent. CFA supports the new proposed organization of EMSs into four domains. Regarding concurrent validity, each schema in the YSQ-S3 was highly correlated with anxiety and mood symptoms. The new four-domains model of the YSQ-S3 has demonstrated that it can be a useful and valid tool for clinicians and researchers in the self-report measurement of EMSs.